Challenges in risk assessment with rural domestic violence victims: implications for practice - Youngson, Nicole (Journal of family violence, 2021)
Through interviews the present study examined the perspectives of service providers (n = 14) in the violence against women (VAW) sector regarding risk factors and challenges in assessing risk for women experiencing domestic violence (DV) in rural locations. The present study also examined what promising practices VAW service providers are utilizing when working with women experiencing DV in rural locations. Interviews were coded and analyzed in a qualitative analysis computer program. Analysis indicated several risk factors including the location (i.e., geographic isolation, lack of transportation, and lack of community resources) and cultural factors (i.e., accepted and more available use of firearms, poverty, and no privacy/anonymity). Moreover, analyses indicated several challenges for VAW service providers assessing risk including barriers at the systemic (i.e., lack of agreement between services), organizational (i.e., lack of collaboration and risk assessment being underutilized/valued), and individual client (i.e., complexity of issues) level. However, participants outlined promising practices being implemented for rural locations such as interagency collaboration, public education, professional education, and outreach programs. The findings support other research in the field that highlight the increased vulnerability of women experiencing DV in rural locations and the added barriers and complexities in assessing risk for rural populations. Implications for future research and practice include further examination of the identified promising practices, a continued focus on collaborative approaches and innovative ways to prevent and manage risk in a rural context.